1995
DOI: 10.1111/j.1540-8159.1995.tb06989.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Pressure and Experimental Atrial Fibrillation

Abstract: A possible profibrillatory effect on the atria of an elevated atrial pressure and the site of atrial stimulation was examined. In 15 anesthetized dogs, right or left atrial or biatrial pacing was applied at a high rate (300-600/min) for 5 seconds at double threshold intensity under a wide range of atrial pressures achieved by venous or arterial transfusion or bleeding. Induction of atrial fibrillation in 236 of 1,971 pacing runs was associated with a significantly higher (P < 0.001) atrial pressure (21.6 +/- 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…The thinned areas of atrial myocardium are vulnerable to stretch caused by increased filling pressures (30). Myocyte stretch increases the atrial effective refractory period dispersion through mechano-electrical feedback and, amplified by collagen deposition, lowers the arrhythmogenic threshold (31,32). These observations have been confirmed in community-based cohorts using diastolic dysfunction as a surrogate for elevated filling pressures to predict nonsurgery-related AF (33).…”
Section: Discussionmentioning
confidence: 81%
“…The thinned areas of atrial myocardium are vulnerable to stretch caused by increased filling pressures (30). Myocyte stretch increases the atrial effective refractory period dispersion through mechano-electrical feedback and, amplified by collagen deposition, lowers the arrhythmogenic threshold (31,32). These observations have been confirmed in community-based cohorts using diastolic dysfunction as a surrogate for elevated filling pressures to predict nonsurgery-related AF (33).…”
Section: Discussionmentioning
confidence: 81%
“…Atrial dilatation caused by volume loading and AV interval manipulation in dogs is associated with heterogenous increases in atrial ERPs, interatrial conduction delays, and a propensity to AF. 5,18,19 A nonsignificant prolongation of atrial refractoriness has also been demonstrated after short-term volume loading in goats. 26 In contrast, short-term increases in atrial pressure in an isolated rabbit model resulted in susceptibility to AF and shortening of atrial ERPs.…”
Section: Electrical Remodeling Associated With Atrial Dilatationmentioning
confidence: 95%
“…These investigators showed that less fibrosis was found in the group pretreated with candesartan than those in the control group. In animal studies, it has been reported that high atrial pressure directly reduced atrial refractoriness and increased refractoriness dispersion, resulting in increased vulnerability to AF [23,24,25]. It has been demonstrated that ACE and extracellular signal-regulated kinase (Erk)1/Erk2levels were increased in patients with AF [26], and that an angiotensin II type 1 receptor antagonist decreases atrial pressure.…”
Section: Discussionmentioning
confidence: 99%